Ruby programming fundamentals - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2016)
"There are some programming languages that require seemingly endless lines of code to make the smallest of programs. There are some languages that are so complex even experts' heads hurt if they try to use them. And then there's Ruby, which has all of the performance of these aforementioned languages and none of the complexity. Productive, powerful, simple and easy to learn, it's the perfect starter language. Oh, and a huge (and growing) number of companies use it too."--Resource description page.
Title and publication information from resource description page (Safari, viewed November 1, 2016).
Keywords: Ruby (Computer program language); Object-oriented programming (Computer science); Electronic books